If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5 + 7x) = -40 + 4x (5 * -3 + 7x * -3) = -40 + 4x (-15 + -21x) = -40 + 4x Solving -15 + -21x = -40 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + -21x + -4x = -40 + 4x + -4x Combine like terms: -21x + -4x = -25x -15 + -25x = -40 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + -25x = -40 + 0 -15 + -25x = -40 Add '15' to each side of the equation. -15 + 15 + -25x = -40 + 15 Combine like terms: -15 + 15 = 0 0 + -25x = -40 + 15 -25x = -40 + 15 Combine like terms: -40 + 15 = -25 -25x = -25 Divide each side by '-25'. x = 1 Simplifying x = 1
| 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 | | 18.75+x=26.55 | | 4x-8=5x+5+75 | | 6x-2x+60= | | 2(3d-4)=2(2d+6) | | y=-3+2+5 | | (3v+5)(8+v)=0 | | 3r-18=3 | | K^2+7x=0 | | -13/5+21/2x=-29/40 | | 25(-8)= | | 2a-6+25=10a | | x+50+x+40+90=180 | | 5r+25=40 | | 6x-7=-2x-9 | | b+10=2b-20 | | bx-a=ac | | 10x=ex-28 | | v^4-13v^3+36v^2=0 | | 15*ln(1+.5x)=ln(2+15x) | | 2(2x+1)=3x-4(1-x) | | 6x+24=6x+12 | | y+y^2+1=14 | | -18(-4)= | | 1.3x-0.28=-2.1 | | 48n-9n^2=36 | | -13+y+y^2=0 | | 0=5x^4-2x^2-4 | | -400.00x+4000=0.00 | | -b+ax=cb |